2017
DOI: 10.1186/s12906-017-1835-8
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Cynara scolymus leaves extract on metabolic disorders and oxidative stress in alloxan-diabetic rats

Abstract: BackgroundDiabetes mellitus (DM) is associated with hyperglycemia, inflammatory disorders and abnormal lipid profiles, currently the extracts from leaves of cynara scolymus has been discovered to treat metabolic disorders and has been stated by multitudinous scientists according to a good source of polyphenols compounds. The present study aimed to evaluate the protective effect of the ethanol leaves extract of C. scolymus in alloxan induced stress oxidant, hepatic-kidney dysfunction and histological changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 59 publications
5
58
0
7
Order By: Relevance
“…The antioxidant activity of artichoke has also been demonstrated in experimental studies (Gebhardt, ; Gebhardt & Fausel, ; Brown & Rice‐Evans, ; Perez‐Garcia, Adzet, & Canigueral, ; Zapolska‐Downar et al, ; Rahimuddin, Khoja, Zuhair, Howell, & Brown, ; Juzyszyn, Czerny, Pawlik, & Drozdzik, ; Miccadei et al, ; Löhr, Deters, & Hensel, ; Mileo, Di Venere, Abbruzzese, & Miccadei, ; Takei et al, ; Miláčková, Kapustová, Mučaji, & Hošek, ; Jiménez‐Escrig, Dragsted, Daneshvar, Pulido, & Saura‐Calixto, ; Goñi, Jiménez‐Escrig, Gudiel, & Saura‐Calixto, ; Mehmetcik, Ozdemirler, Kocak‐Toker, Cevikbas, & Uysal, ; Kucukgergin et al, ; Kusku‐Kiraz, Mehmetcik, Dogru‐Abbasoglu, & Uysal, ; Heidarian, Jafari‐Dehkordi, & Seidkhani‐Nahal, ; Heidarian & Soofiniya, ; Song et al, ; Heidarian & Rafieian‐Kopaei, ; Abdel‐Kader et al, ; Al‐Ahdab, ; Magielse et al, ; El Morsy & Kamel, ; Najim, Numan, & Hamad, ; Colak et al, ; Jaleel, Saleh, & El‐Awdan, ; Khattab, Wazzan, & Al‐Ahdab, ; Mocelin et al, ; Ben Salem et al, ; El‐Boshy et al, ; Kaymaz, Kandemir, Pamukçu, Eröksüz, & Özdemir, ; Tang, Wei, Deng, & Lei, ).…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…The antioxidant activity of artichoke has also been demonstrated in experimental studies (Gebhardt, ; Gebhardt & Fausel, ; Brown & Rice‐Evans, ; Perez‐Garcia, Adzet, & Canigueral, ; Zapolska‐Downar et al, ; Rahimuddin, Khoja, Zuhair, Howell, & Brown, ; Juzyszyn, Czerny, Pawlik, & Drozdzik, ; Miccadei et al, ; Löhr, Deters, & Hensel, ; Mileo, Di Venere, Abbruzzese, & Miccadei, ; Takei et al, ; Miláčková, Kapustová, Mučaji, & Hošek, ; Jiménez‐Escrig, Dragsted, Daneshvar, Pulido, & Saura‐Calixto, ; Goñi, Jiménez‐Escrig, Gudiel, & Saura‐Calixto, ; Mehmetcik, Ozdemirler, Kocak‐Toker, Cevikbas, & Uysal, ; Kucukgergin et al, ; Kusku‐Kiraz, Mehmetcik, Dogru‐Abbasoglu, & Uysal, ; Heidarian, Jafari‐Dehkordi, & Seidkhani‐Nahal, ; Heidarian & Soofiniya, ; Song et al, ; Heidarian & Rafieian‐Kopaei, ; Abdel‐Kader et al, ; Al‐Ahdab, ; Magielse et al, ; El Morsy & Kamel, ; Najim, Numan, & Hamad, ; Colak et al, ; Jaleel, Saleh, & El‐Awdan, ; Khattab, Wazzan, & Al‐Ahdab, ; Mocelin et al, ; Ben Salem et al, ; El‐Boshy et al, ; Kaymaz, Kandemir, Pamukçu, Eröksüz, & Özdemir, ; Tang, Wei, Deng, & Lei, ).…”
Section: Introductionmentioning
confidence: 80%
“…Furthermore, antioxidant properties of artichoke leaf extract have been revealed in diabetic rats. Supplementation with extract of artichoke leaf resulted in significant reduction of MDA and advanced oxidation protein product (AOPP) level and significant increase in the activity of CAT and SOD and level of GSH and ferric reducing/antioxidant power (FRAP) in supplemented group compared with the nonsupplemented group (Ben Salem et al, ; Heidarian & Soofiniya, ). In another study, Magielse et al () assessed the effects of two doses of aqueous artichoke leaf extract (200 mg/kg and 1,000 mg/kg) on oxidant and antioxidant markers in streptozotocin‐induced diabetic rat model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The artichoke leaves are well known for their beneficial therapeutic effects in enhancing lipid metabolism, choleresis, and hepatic functions. In several studies, the extracts from artichoke leaves showed also decreasing activities of glucose level and beneficial effect on lipid metabolism of diabetic rats (Hosseini et al, ; Magied et al, ; Salem et al, ) as well as effective AKR1B1 and RL‐AKR inhibitions (Miláčková et al, ). Human AKR1B1 (and rat equivalent RL‐AKR) is the first enzyme of the polyol pathway that reduces glucose to sorbitol more intensively under diabetic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The artichoke leaves were investigated for their beneficial effects (mainly due to polyphenolic compounds) such as inhibition of the biosynthesis of cholesterol, induction of choleresis, mobilization of energy reserves, as well as their antibacterial and hepatoprotective actions (Gabbay, ; Zhu, Zhang, & Lo, ). Artichoke extracts are also recognized for their hypoglycemic effect and beneficial effect on lipid metabolism of diabetic rats (Hosseini, Mousaei, & Tavakoli, ; Magied, Hussien, Zaki, & Said, ; Salem et al, ).…”
Section: Introductionmentioning
confidence: 99%